Compliance of listed companies with codes of corporate governance and its impact on corporate performance: A comprehensive analysis of current Sri Lankan evidence - Dissanayake, D.H.S.W.; Dissabandara, D.B.P.H.; Ajward, A.R. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This study examines the nature and the level of compliance with corporate governance best practices in Sri Lankan listed companies and the relationship between the level of compliance and the firm’s performance in Sri Lanka. The main objective was to measure corporate governance using the Corporate Governance Index (CGI) and to examine the relationship between corporate governance and corporate performance. This study also examines 18 sub-samples based on the sectors and identifies the changes in compliance level. It was conducted as a quantitative study based on the annual reports of 133 public listed companies in 18 sectors in the period 2009-2016. The data covered five corporate governance categories: Board of Directors, Shareholders, Chief Executive Officer (CEO) and Management, Communication and Disclosure, and Stakeholders. Informal interviews were conducted with experts to obtain the weights to measure the CGI. The unit of analysis was firm year. Panel data analysis was used to test the hypothese after conducting Diagnosis Tests and Hausman Test. This study developed a CGI based on governance practices followed by the listed companies to achieve this objective. The results provide an in-depth understanding based on a large sample and the analysis indicates a significant positive relationship between financial performance in terms of Return on Equity and Return on assets and a negative relationship with market performance in terms of Tobin’s Q. The analysis further reveals a positive relationship between the stakeholder sub-index, the CEO and management sub-index and the communication and disclosure sub-index and corporate performance. The sectoral analysis shows that the compliance level differs across sectors.
Keywords: Corporate governance index, stakeholder sub-index, CEO and management sub-index, communication and disclosure sub-index, Sri Lanka